Pengaruh Pengembangan Metode Problem Based Learning (PBL) terhadap Kemampuan Berfikir Kritis pada Mata Pelajaran IPA Kelas IV SD 1 Mardiatul Islamiyah - Anggi Putri Wahyuni; Audi Reyhan Anjani Purba; Rezky Cahyani Harahap (Journal on Education, 2023)
This study aims to see whether there is an effect of learning development using the Problem Based Learning (PBL) method on critical thinking skills in grade IV science subjects at SD 1 Mardiatul Islamiyah. This research includes quantitative research using a quasi-experimental research design. This study was designed using an experimental class and a control class based on the pretest-posttest design experimental research. The results showed that the average posttest result of the experimental group was 75 and that of the control group was 63.3. The results are in a different category. However, there was an increase in the average value of the experimental group by 38.4 which was higher than the increase in the average value of the control group by 26.7